Ruusbroec's mystical vision in Die gheestelike brulocht seen in the light of Minne - Wiseman, James A., 1942- (Fiery arrow collection, 2018)
In his masterwork, 'Die geestelijke brulocht' (The Spiritual Espousals), the fourteenth-century Flemish mystic Jan van Ruusbroec used his profound knowledge of Trinitarian theology to show that the apex of the spiritual life consists in our being taken up into the love of the three persons of the blessed Trinity. The care and precision with which Ruusbroec describes the ascent from "the active life" to "the interior life" and from there to the culmination of "the contemplative life" is evident in the way he carefully distinguishes between three terms that could all be translated as "love": minne, karitate, and liefde. James Wiseman's astute reading of Ruusbroec's treatise shows how the affective aspect of love (liefde) and the aspect that expresses itself in virtuous activity (karitate) are both subsumed under the all-embracing reality of minne, the love that flows forth from the triune God and then draws us back to a blissful reunion with our loving Source